Komasacija u funkciji poljozaštitnih šumskih pojaseva u Republici Srbiji - kritički osvrt Land consolidation in the function of shelterbelts for agricultural land in the Republic of Serbia - critical review - Marinković, Goran; Grgić, Ilija, inženjer geodezije; Lazić, Jelena; Trifković, Milan (2020)
U ovome radu prikazani su rezultati analize realizacije poljozaštitnih šumskih pojaseva u postupku komasacije. Istraživanjem su obuhvaćena tri karakteristična projekta komasacije u Autonomnoj pokrajini Vojvodini, kroz čije provođenje je trebalo realizirati i projekte poljozaštitnih šumskih pojaseva. S obzirom da se izabrani projekti nalaze u različitim dijelovima područja istraživanja, zaključci izvedeni u ovome radu mogu se smatrati reprezentativnim za teritorij Vojvodine. Studija je pokazala da nije iskorištena prilika za povećanjem šumovitosti Vojvodine, odnosno da projekti poljozaštitnih šumskih pojaseva nisu uopće razmatrani u postupku komasacije ili ako su i uzimani u obzir, zemljište odvojeno za njih nikad nije privedeno namjeni.
The forests as a necessary condition for human civilization existence also are of great ecological and economic importance. This fact is often neglected in practice despite the fact on wide spread scientific knowledge about it. The authors noticed that practice and made research about shelterbelts realization in the numerous cases of theoretical researches as well as in projects of land consolidation projects in Serbia (mostly of them provided in Autonomous Province of Vojvodina as a region where agricultural land dominates). The benefits of shelterbelts are well known from scientific literature and practice for agricultural land protection, but the realization of them in concrete projects are connected with a lot of obstacles. In this paper more than the author ivestigated the projects of land consolidation from the aspect of the chances for building shelterbelts and their realization in practice. The research provided on more than eight hunderd projects of land consolidation has shown that only in a few of them the shelterbelts were forseen and no one of them was realized as designed. The reasons are mostly connected with the resistance of participants in land consolidation to give up of their land for shelterbelts building, with lack of capacities for seedlings providing and with the insufficient attention paid to this issue in legal regulation. In this paper the results of analysis of shelterbelts in the process of land consolidation are shown. Research encompassed three different and distinguished projects of land consolidation in Autonomous Province of Vojvodina - The Republic of Serbia, through which realization was required to provide the projects of shelterbelts. Bearing in mind that chosen projects are spread in different geographical areas of research fields, the conclusions obtained in this paper could be considered as representative for Vojvodina. The Vojvodina is especcialy interesting for research because this region is lacking with forest.
Bibliografija: str. 176-177.
Sažetak ; Summary.
Keywords: Šume -- Eolska erozija -- Komasacija; Srbija